Unfastening Sublethal Effects of the Nematophagus Fungus Pochonia chlamydosporia [TNAU Pc-001] on the Biotic Potentials of Meloidogyne enterolobii (Yang & Eisenback, 1983) (Tylenchida: Meloidogynidae) - Arunachalam, Arun; Ganesan, Shandeep; Pandiyan, Vetrivelkalai; Palaniyappan, Kalaiarasan; Nagachandrabose, Seenivasan; Kandasamy, Devrajan (Gesunde Pflanzen, 2025)
Meloidogyne enterolobii, the root-knot nematode which triggers root galls, is a very destructive species that has a substantial impact on agricultural crops all over the world. Due to this nematode’s resistance of conventional chemical control techniques, it is necessary to investigate sustainable alternatives such biological control agents. An investigation was conducted to find out how the nematophagous fungus Pochonia chlamydosporia influencing the characteristics of M. enterolobii’s life table and population dynamics. Age-stage, two-sex life tables were constructed to compare the control and treated groups. The results demonstrated significant reduction in key population parameters in the treated group, including lower net reproductive rate (R0), intrinsic rate of increase (r) and finite rate of increase (λ). The mean generation time (T) was shorter in the treated group indicating a faster generational turnover. Additionally, reproductive value (vij) and life expectancy (exj) were lower in the treated group, reflecting decreased future reproductive potential and survival. The aforementioned results demonstrate the efficacy of P. chlamydosporia in inhibiting the populations of M. enterolobii and bolster its prospective application as a viable biocontrol tactic. The integration of this technique with other sustainable agriculture methods and its long-term implications should be the subject of future investigation.